2022
DOI: 10.1177/03635465211072562
|View full text |Cite
|
Sign up to set email alerts
|

Double-Bundle Versus Single-Bundle Anterior Cruciate Ligament Reconstruction in Patients With Significant Passive Anterior Tibial Subluxation

Abstract: Background: Passive anterior tibial subluxation (PATS) is often observed in patients with anterior cruciate ligament tears. Postoperative outcomes of double-bundle (DB) and single-bundle (SB) anterior cruciate ligament reconstruction (ACLR) with significant PATS (>6 mm) are unclear. Hypothesis: DB-ACLR could achieve better stability and clinical outcomes than SB-ACLR in patients with PATS >6 mm. Study Design: Cohort study; Level of evidence, 3. Methods: Retrospective analysis was peformed on 626 consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Notably, most patients in the current study were non‐professional athletes with chronic ACL tears, and it is difficult to compare their outcomes with those in the aforementioned studies due to different demographic characteristics, preoperative instability, surgical techniques, and sports levels. Lin et al [20] compared DB‐ACLR with SB‐ACLR in patients with excessive anterior tibial subluxation and concluded that DB‐ACLR resulted in better knee stability and patient‐reported outcomes; however, the equivalent graft diameter of DB‐ACLR (6–8 strands of hamstrings) was larger than that of SB‐ACLR (HT4), which may be a major confounder. Further studies are warranted to compare the two techniques in the premise of comparable graft sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, most patients in the current study were non‐professional athletes with chronic ACL tears, and it is difficult to compare their outcomes with those in the aforementioned studies due to different demographic characteristics, preoperative instability, surgical techniques, and sports levels. Lin et al [20] compared DB‐ACLR with SB‐ACLR in patients with excessive anterior tibial subluxation and concluded that DB‐ACLR resulted in better knee stability and patient‐reported outcomes; however, the equivalent graft diameter of DB‐ACLR (6–8 strands of hamstrings) was larger than that of SB‐ACLR (HT4), which may be a major confounder. Further studies are warranted to compare the two techniques in the premise of comparable graft sizes.…”
Section: Discussionmentioning
confidence: 99%
“…For hamstring autografts, an increase in the graft diameter between 7 and 10 mm usually results in a lower rate of ACLR failure and revision surgery [17,18]. Furthermore, double-bundle (DB) ACLR may be superior to single-bundle (SB) ACLR in restoring anteroposterior and rotatory stability and reducing the clinical failure rate [20][21][22]. Some researchers have applied a strategy of preparing eight strands of hamstring (HT8) autografts, comprising the 4-stranded ST and 4-stranded GT, to increase the total graft size of DB-ACLR and improve knee stability [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…No prophylactic antibiotics were administered. Meanwhile, arthroscopic single-bundle ACL reconstruction was performed by the same surgeon as previously described [ 18 ]. In brief, tourniquet was routinely used during the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…A standard institutional MRI examination with a 1.5-T superconducting magnet (Optima MR360; GE) was performed. Electronic measurements were performed by observers to determine anterior subluxation in the lateral tibial compartment relative to a posterior femoral condylar reference line on sagittal MRI scans, as first described and validated by Iwaki et al 18 and later utilized by Tanaka et al 44 This technique was also used by Song et al 42 and Lin et al 25 The amount of PATS was measured on the MRI scans within 2 months preoperatively.…”
Section: Mri Measurement Of Patsmentioning
confidence: 99%